Trespassers and Existential Import. (6th February 2019) - Wong, Kai‐Yee; Hung, Chi‐Ho
Abstract : It is a received view of the post‐Fregean predicate logic that a universal statement has no existential import and thus does not entail its particular (existential) counterpart. This paper takes issue with the view by discussing the trespasser case, which has widely been employed for supporting the view. The trespasser case in fact involves a shift of context. Properly understood, the case provides no support for the received view but rather suggests that we rethink the 'quantity view' of the existential import of quantifiers